Tinjauan Yuridis Peralihan Hak Milik Atas Tanah Melalui Akta Hibah di Hadapan Notaris - Intan Novitasari (Lembaga Pengembangan Kinerja Dosen, 2025)
The transfer of land ownership rights through a grant (hibah) is a form of voluntary and non-compensatory property transfer. Notaries play a crucial role in drafting grant deeds to ensure legal certainty and protect the rights of the parties involved. This study aims to analyze the legal aspects of land ownership transfer through a grant deed before a notary, as well as the legal strength of the grant deed in providing legal certainty. The research employs a normative juridical method with a statutory and conceptual approach. The findings indicate that a grant deed executed before a notary holds perfect evidentiary power and serves as a crucial requirement in the process of transferring land ownership titles at the land office.